2015
DOI: 10.1002/ange.201506559
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric [3+2] Annulation Approach to 3‐Pyrrolines: Concise Total Syntheses of (−)‐Supinidine, (−)‐Isoretronecanol, and (+)‐Elacomine

Abstract: An asymmetric [3+ +2] annulation reaction to form 3-pyrroline products is reported. Upon treatment with lithium diisopropylamide,r eadily available ethyl 4-bromocrotonate is deprotonated and trapped with Ellman imines selectively at the a-position to yield enantiopure 3-pyrroline products.This new method is compatible with aryl, alkyl, and vinyl imines.T he efficacy of the method is showcased by short asymmetric total syntheses of (À)-supinidine,(À)-isoretronecanol, and (+ +)-elacomine.T his novel annulation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Inspired by Ellman's pioneering work, 53 we eventually decided to construct β-amino ester 75 from allylated valerolactone 76 54 and N-tertbutanesulfinyl imine 77. 55 Cursory examination of the parameters for this transformation had shown that the γsubstituent in the imine would be required to avoid undesired 1,4-addition of the enolate. 29 While we faced some uncertainty regarding the diastereoselectivity at the α-quaternary center in this Mannich reaction, we reasoned that the choice of these particular substrates would be ideal in terms of accessing a suitably functionalized and oxidized product for rapid conversion to 75.…”
Section: Scheme 3 Synthesis Of Alkyne 29 a Amentioning
confidence: 99%
See 2 more Smart Citations
“…Inspired by Ellman's pioneering work, 53 we eventually decided to construct β-amino ester 75 from allylated valerolactone 76 54 and N-tertbutanesulfinyl imine 77. 55 Cursory examination of the parameters for this transformation had shown that the γsubstituent in the imine would be required to avoid undesired 1,4-addition of the enolate. 29 While we faced some uncertainty regarding the diastereoselectivity at the α-quaternary center in this Mannich reaction, we reasoned that the choice of these particular substrates would be ideal in terms of accessing a suitably functionalized and oxidized product for rapid conversion to 75.…”
Section: Scheme 3 Synthesis Of Alkyne 29 a Amentioning
confidence: 99%
“…The dried solution was filtered, and the filtrate was concentrated in vacuo. The crude residue was purified by flash column chromatography (40% ethyl acetate in hexanes) to give alkynone 54 (685 mg, 1.97 mmol, 97% over two steps, 1,143.2,140.3,140.3*,137.7,136.11*,136.10,95.5,77.79*,77.77,72.8,43.2,40.7,37.5,33.1,31.8,28.9,23.93,23.91*,16.9,15.17*,15.16,15.10*,neat) Synthesis of 2-((S)-5-Allyl-7-methyl-5-azaspiro[2.4]heptan-4-ylidene)-1-((R)-2,6,7,7a-tetrahydro-1H-inden-5-yl)ethan-1-one (55). A solution of alkynone 54 (2.09 g, 6.03 mmol, 1.0 equiv, ∼3:1 d.r.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inspired by the structural homology of the kainoid natural products, and the reliability and flexibility of our recently disclosed method for assembling chiral 3‐pyrrolines, we postulated that these kainoids could be rapidly assembled from a common precursor. To establish the feasibility of our synthetic hypothesis we chose to first study kainic acid.…”
Section: Introductionmentioning
confidence: 99%
“…While Ellman’s pioneering studies have revealed that adding ester enolates to N - tert -butanesulfinyl imines result in good diastereoselectivities at the β -amino stereocenter, 19 the selectivity outcome at the α -center remains difficult to predict when fully substituted, unsymmetrical enolates are employed. Following an initial survey of imines and enolates, 20 allylated valerolactone 8 21 and sulfinyl imine 9 22 were identified as suitable precursors (Scheme 1). Thus, reaction of 9 with the lithium enolate derived from 8 led to an intriguing Mannichretro–Mannich equilibration of the β -amino lactones ( SS - 10 and SR - 10 ), and optimization studies eventually yielded an ~1:1 mixture of C8 epimers in 82% combined yield on multigram scale.…”
mentioning
confidence: 99%